Mimicry of Chinese Identity in American Born Chinese Written By Gene Leun Yang - Nur Iklima Dewi (ELITE: Journal of English Language and Literature, 2019)
America is a country of nations. Despite of issue of discrimination, the formation of immigrant also has colored America as multicultural society. This study aims at describing the mimicry of Chinese identity in the American Born Chinese graphic novel published in 2006 written by Gene Leun Yang. This research used a descriptive qualitative method, and Homi K. Bhabha's postcolonial theory is used as a tool analysis. The study found that the American Born Chinese graphic novel featuring Chinese immigrants from different social and ethnic backgrounds shows the process of forming a mimicry culture in the United States. It Shown through a Chinese boy named Jin Wang, who combines Chinese and American culture. This can be seen: mimicry in the Chinese racial identity and mimicry in Chinese ethnicity identity. From these two things, mimicry culture can be formed because of the process of ambivalence. These concepts are one of the formations of mimicry culture. In this study also, researchers analyzed the problem of the stereotype and hybridity process in the object.